2019
DOI: 10.3389/fmicb.2019.00708
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Diversity Suggestive of Distinct Salmonella Typhimurium Sources or Selective Pressures in Food-Production Animals

Abstract: Salmonella enterica subsp. enterica serovar Typhimurium is a common cause of enterocolitis in humans globally, with multidrug resistant (MDR) strains posing an enhanced threat. S. Typhimurium is also a pathogen in food-production animals, and these populations can act as reservoirs of the bacterium. Therefore, surveillance and control measures within food-production animal populations are of importance both to animal and human health and have the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…Many reports have identified high levels of AMR in food animals and retail meats in the United States ( Davis et al, 2018 ; Liu et al, 2018 ), China ( Liu et al, 2017 ; Wu et al, 2018 ; He et al, 2019 ), and Europe ( Gelbíčová et al, 2019 ; Mellor et al, 2019 ). Other studies have assessed ARG dissemination between isolates of human, animal, and environmental origin in LMICs ( Nadimpalli et al, 2019 ; Subbiah et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have identified high levels of AMR in food animals and retail meats in the United States ( Davis et al, 2018 ; Liu et al, 2018 ), China ( Liu et al, 2017 ; Wu et al, 2018 ; He et al, 2019 ), and Europe ( Gelbíčová et al, 2019 ; Mellor et al, 2019 ). Other studies have assessed ARG dissemination between isolates of human, animal, and environmental origin in LMICs ( Nadimpalli et al, 2019 ; Subbiah et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, outbreak strains also showed resistance to NAL. These five antibiotics were the most common antibiotics for which S. Typhimurium exhibited resistance, especially in China Liang et al, 2018;Khan et al, 2019;Mellor et al, 2019). NAL belongs to the first generation of quinolone antibiotics, and many intestinal infecting bacteria have developed resistance to it.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the antibiotic resistance rate of S. Typhimurium has been increasing, making it a global issue of increasing concern that might result in more severe health outcomes (Parisi et al, 2018;Jiu et al, 2020). Some studies have shown that the proportion of multidrug resistant bacteria in S. Typhimurium is very high and the most frequently observed antibiotic resistance patterns are the ASSuT (ampicillin, streptomycin, sulfonamides, and tetracycline) and ACSSuT (ampicillin, chloramphenicol, streptomycin, sulfonamides, and tetracycline) tetra-and penta-resistant patterns, respectively (Thung et al, 2016;Mellor et al, 2019;Wang et al, 2019). Multidrug resistant S. Typhimurium has brought difficulties to clinical treatment resulting in increased morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Whereafter, the variety of antibiotic resistance patterns have been reported. For example, the ASSuT tetra-(ampicillin, streptomycin, sulfonamides, and tetracycline) and ACSSuT (ampicillin, chloramphenicol, streptomycin, sulfonamides, and tetracycline) penta-resistant patterns are the most commonly reported (Mellor et al, 2019;Thung et al, 2016;Wang et al, 2019). Salmonella 4, [5],12:i:-, a monophasic variant of Salmonella Typhimurium, progressively became an emerging multidrug resistant clade carrying plasmid-mediated resistance genes (Elnekave et al, 2018;Mourao et al, 2014) and the sequence types mostly are ST19 and ST34 (Elnekave et al, 2018;Pernille Gymoese et al, 2017;Sun et al, 2020).…”
Section: Introductionmentioning
confidence: 99%